Methods of Nominating in Animal Proper Names (Zoonyms) - Frankowska-Kozak, Božena (Respectus Philologicus, 2002)
The aim of this paper is to present the result of linguistic research into the process of name-giving and tendencies concerning animal proper names. ’Zoonyms are currently a productive group of proper names’, the creation of which is conditioned by such factors as cultural awareness, tradition and fashion. With the help of the Questionnaire for Investigating Rural Zoonymy in Poland (Against the Synchronic Background) designed by S. Warchoł2 the linguistic data was collected among the citizens of rural West Pomerania in the years 1993 - 2000. Four age groups replied to the questionnaire (group 1: senior citizens aged 60+, group 2: aged 40 - 60, group 3: aged 20 - 40, group 4: aged below 20). They belonged to different dialectal groups.